METALLOPROTEASES AND INHIBITORS EXPRESSION IN MYOCARDIUM UNDER ISCHEMIC CONDITIONS AFTER ALLOGENIC BIOMATERIAL INTRODUCTION - A. I. Lebedeva; S. A. Muslimov; E. M. Gareev; S. V. Popov; S. A. Afanasyev; D. S. Кondratyeva (Российский кардиологический журнал, 2018)
Aim. To assess the expression of ММР-9 and TIMP-2 after intramyocardial injection of the allogenic biomaterial (AB) into ischemized myocardium in rodents.Material and methods. One hundred Wistar rodents were used, who underwent ligation of coronary artery. The experiment group (n=50), together with coronary occlusion, received the suspension of AB 12 mg. General histology was applied: hematoxyline and eosine, by Mallori; immune histochemistry (ММP-9, TIMP-2, CD68); morphometry: index of the scar area (ISA), amount of ММP-9, TIMP-2, CD68-positive cells.Results. It was shown that in the experimental group, after implantation of AB there were lesser than in controls values of ISA (2,74 times, p<0,05 . <0,0001), numbers of MMP9+ cells (p<0,001) and macrophages CD68+ (p<0,05), as the manifestation of proteolysis and area of lesion. On the contrary, amount of Timp-2+ cells in the experimental group was higher than in the control (p<0,0004).Conclusion. Resorption of allogenic material (Alloplant) products does influence the balance of metalloproteinases and their inhibitors in the myocardium after ischemic lesion. This effect might influence the processes of myocardial remodelling and scar formation.